The Authority of Public Prosecutor in Stopping the Prosecution of Criminal Cases based on Restorative Justice - Yeriza Adhytia; Arpangi Arpangi; Rakhmat Bowo Suharto (Law Development Journal, 2022)
The purpose of this study consists of 3 (three) aspects, the first is to analyzePublic Prosecutor's Authority in stopping the prosecution of criminal cases on the basis of restorative justice. The second objective is to analyze the mechanism for stopping the prosecution of criminal cases on the basis of restorative justice. The third objective is to analyze the inhibiting factors in carrying out the termination of prosecution of criminal cases on the basis of restorative justice. The research approach method used is sociological juridical. The conclusion of this research is, first the prosecutor's authority to stop prosecution of a criminal case based on the Termination of Prosecution Perja is a form of attribution authority. Second, the mechanism for stopping prosecution based on restorative justice is carried out within a period of 14 (fourteen) days after receiving the handover of responsibility for the suspect and evidence from the investigator which consists of several stages as stipulated in the Perja on Termination of Prosecution. Third, the most dominant obstacle in the process of discontinuing prosecution based on restorative justice is the statutory factor, namely: short period of time in Dismissal of Prosecutionnot commensurate with the length of the mechanism that must be taken as well as cultural factors, namely the low awareness of the culture of forgiveness by the Victim towards the Suspect which has an impact on the inability to carry out the peace process.